Application of whole-genome sequencing to detect antibiotic resistance in Gram-negative bacteria - Manageiro, Vera (2018)
Antibiotic resistance is an emerging problem, becoming a serious threat to global public health. The causes of its spread are complex, as are the strategies to combat this threat. Following recent improvements in sequencing technologies, whole-genome sequencing (WGS) provides a comprehensive alternative in the evaluation and detection of antibiotic resistance mechanisms. In the scope of the analysis of nonsusceptibility of Gram-negative isolates recovered from human, veterinary and environment samples, we identified the presence of a high diversity of resistance mechanisms. To understand the genetic background of those resistance mechanisms, which included oxyimino-β-lactam, fluoroquinolone and colistin resistance-encoding genes, we performed whole genome and plasmid sequencing using a 454 (Roche) and/or MiSeq (Illumina) sequencing strategy. A set of bioinformatic web tools were used to estimate the presence of pathogenicity determinants, antibiotic resistance (AR) genes, and clinically relevant mobile genetic elements. Indeed, the efficient gene capture and spread of resistance determinants by mobile genetic elements are factors to be taken into account, due to their contribution for the co-selection of multidrug resistant strains in the different settings and environment. Furthermore, WGS might be used with great benefit in combination with phenotypic methods for surveillance purposes.